Effects of adrenalectomy on daily gene expression rhythms in the rat suprachiasmatic and paraventricular hypothalamic nuclei and in white adipose tissue. (March 2015) - Su, Yan; van der Spek, Rianne; Foppen, Ewout; Kwakkel, Joan; Fliers, Eric; Kalsbeek, Andries
Abstract : It is assumed that in mammals the circadian rhythms of peripheral clocks are synchronized to the environment via neural, humoral and/or behavioral outputs of the central pacemaker in the suprachiasmatic nucleus of the hypothalamus (SCN). With regard to the humoral outputs, the daily rhythm of the adrenal hormone corticosterone is considered as an important candidate. To examine whether adrenal hormones are necessary for the maintenance of daily rhythms in gene expression in white adipose tissue (WAT), we used RT-PCR to check rhythmic as well as 24 h mean gene expression in WAT from adrenalectomized (ADX) and sham-operated rats. In addition, we investigated the effect of adrenalectomy on gene expression in the hypothalamic SCN and paraventricular nucleus (PVN). Adrenalectomy hardly affected daily rhythms of clock gene expression in WAT. On the other hand, >80% of the rhythmic metabolic/adipokine genes in WAT lost their daily rhythmicity in ADX rats. Likewise, in the hypothalamus adrenalectomy had no major effects on daily rhythms in gene expression, but it did change the expression level of some of the neuropeptide genes. Together, these data indicate that adrenal hormones are important for the maintenance of daily rhythms in metabolic/adipokine gene expression in WAT, without playing a major role in clock gene expression in either WAT or hypothalamus.